3s+-8=-22

Simple and best practice solution for 3s+-8=-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3s+-8=-22 equation:


Simplifying
3s + -8 = -22

Reorder the terms:
-8 + 3s = -22

Solving
-8 + 3s = -22

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 3s = -22 + 8

Combine like terms: -8 + 8 = 0
0 + 3s = -22 + 8
3s = -22 + 8

Combine like terms: -22 + 8 = -14
3s = -14

Divide each side by '3'.
s = -4.666666667

Simplifying
s = -4.666666667

See similar equations:

| 5z^3/z^6=0 | | y=2xp+x^2p^4 | | 4(4x+4)=18x+2 | | 2b+9b=3 | | 3x+8x-9+6-3x=2x+8-9x-3 | | 15=b-(-63) | | .13(4x+2)=.05x+6 | | 5X-15-2=23 | | 1-4x=19-x | | 5x+2y=c | | 7/12-3/8×(9/4)^-1 | | 58+n=58 | | x^2+12x=360 | | 140=(2x+2)(x+4) | | (4x-2)x+78=180 | | 1/3((3.14*(1^2)3) | | 70=(2x+2)(x+4) | | 150w+2=195w-1 | | 2x+0=-6y | | 35=(2x+2)(x+4) | | 12=6(x+1)-8(1-y) | | 1/6p-7=9 | | 24-7p=-6(-4-7p) | | 2x+0=6y | | 2y=-12+6x | | 10x+4+14x=28 | | 1.4x+6=19 | | 7(4x+1)=5x-8x | | dx+(x+2xy^2-2y)dy=0 | | 2/7x=y | | X/4-1.10=4 | | 3(x+3)=6(x-1)-6 |

Equations solver categories